The Mediating Role of Resilience and Self-Esteem Between Life Events and Coping Styles Among Rural Left-Behind Adolescents in China: A Cross-Sectional Study - Li, Juan; Chen, Yi-ping; Zhang, Jie; Lv, Meng-meng; Välimäki, Maritta; Li, Yi-fei; Yang, Si-lan; Tao, Ying-xiang; Ye, Bi-yun; Tan, Chu-xia; Zhang, Jing-ping (Frontiers in Psychiatry, 2020)
A large amount of scientific evidence demonstrates that life events have a huge psychological and social impact on adolescents. Due to lack of companionship of parents, left behind adolescents suffer from more life events compared with non-left behind adolescents. While a direct relationship between life events and coping styles has been observed, indirect effects have not been examined. Therefore, the aim of this study was to explore the association between life events and coping styles and how resilience and self-esteem mediate this association. Adopting two-step stratified random sampling and using region, county as sampling framework, we utilized self–designed socio–demographic questionnaire, Adolescent Self-Rating Life Events Check List, the Resilience Scale Chinese Adolescent, Rosenberg Self-esteem Scale and Simplified Coping Style Questionnaire to assess the mental health of 1,000 left behind adolescents in five junior high schools in Hunan Province，China. Statistic description, Structural equation model was adopted to analyze the data. The results reveal that life events could negatively predict resilience(β=-0.29, P <0.001), self-esteem (β =-0.39, P <0.001), and positively predict LBAs’ positive coping style (β = 0.28, P <0.001) and negative coping style (β = 0.21, P <0.001). Self-esteem could also positively predict the resilience of LBAs (β = 0.62, P <0.001), resilience could negatively predict the negative coping style (β =-0.21, P <0.001), and positively predict the positive coping style (β = 0.79, P <0.001).Life events can not only directly influence the negative coping style (β = 0.21) and positive coping style (β = 0.28), but also can indirectly influence coping styles by affecting resilience (β = -0.29) and self-esteem (β = − 0.39). The total effect of life events on coping styles was 0.32, where 34.37% was mediated by resilience and self-esteem. In this research we proved that resilience and self-esteem mediated most of the effect of life events on coping styles. The findings had important implications for interventions to promote mental health of LBAs, particularly the enhancement of resilience and self-esteem.